Brewing characteristics of 4 kinds of highland barley malt based on variation coefficient method - WANG Min, BAI Shuqun, MEI Yu, ZHENG Xueling (Zhongguo niangzao)
In order to explore the adaptability of highland barley malt as beer raw material, the physicochemical indexes, functional indexes and volatile flavor compounds of 4 kinds of highland barley (black highland barley, Ganqing No. 4, Chaiqing No. 1, Dulihuang) malt were detected and compared. The comprehensive score was obtained by the coefficient of variation method, and the optimal brewing characteristics of highland barley malt was screened. The results showed that anthocyanin, β-glucan, Kulbach value, β-amylase and reducing sugar accounted for more weight, among which anthocyanin (weight 0.278) was the most important. The comprehensive score results showed that the brewing characteristics of Ganqing No. 4 malt was the optimal (comprehensive score 0.613), followed by Dulihuang malt (comprehensive score 0.320) and black highland barley malt (comprehensive score 0.285), and the brewing characteristics of Chaiqing No. 1 malt was the worst (comprehensive score 0.002). In general, Ganqing No. 4 malt had better brewing characteristics.